Efeitos do benefício previdenciário do segurado especial na dinâmica socioeconômica do Quilombo de Saracura: um estudo de caso - JESUS, Marcos José Oliveira de (Universidade Federal do Oeste do Pará, 2023)
This work aims to analyze the effects of the social security benefit of the special insured on the socioeconomic dynamics of Quilombo de Saracura. This is an empirical research of a quali-quanti character based on descriptive analysis. Based on the theoretical framework, it was verified that the Brazilian social security system has undergone several changes, both institutional and normative, and there is still a broad debate around the externalities generated from the expansion of the social security system to the rural sector. From the empirical study, it was found that the benefit represents, on average, 91% of the beneficiaries' family income. Of the value of the benefit, on average, 71% is spent on consumption with food, health, clothing and transport. It was observed that 88% of those interviewed had already accessed payroll-deductible loans, on average, twice. In general, the amount obtained with the credit is intended for the consumption of durable goods, such as: houses, boats, land and renovations. Thus, the benefit guarantees quality in food, health care, improvements in housing, promoting social well-being for the insured. On the other hand, it increases consumption, moves local grocery stores, allows access to credit and improves the means of maritime transport in the quilombo, fostering the local economy.